Teknik Mordanting Ekstrak Kulit dan Biji Terong Belanda (Solanum betaceum Cav.) sebagai Pewarna Alami Tekstil - Melantina Oktriyanti; Idha Silviyati; Nyayu Febrina Nuraini (Yayasan Literasi Sains Indonesia, 2026)
The peel and seeds of tamarillo (Solanum betaceum Cav.) are sources of anthocyanin pigments with potential application as natural dyes for a more environmentally friendly textile industry. The widespread use of synthetic dyes, which still dominates today, poses negative impacts on both the environment and human health. Therefore, this study was conducted to evaluate the quality of the resulting extracts. The parameters assessed included acidity level (pH), anthocyanin content based on UV-VIS absorbance values, color characteristics, and color fastness in accordance with the SNI ISO 105-A03:2010 standard. The results showed that the duration of maceration had a significant effect on the quality of the extracts. For the peel extract, the optimal condition was obtained at pH 3, with an anthocyanin content of 65.12 mg/L, an absorbance value of 0.391, and color fastness at a scale of 4–5, which is categorized as very good. Meanwhile, the seed extract exhibited optimal results at pH 3, with an anthocyanin content of 127.07 mg/L, an absorbance value of 0.761, and color fastness at a scale of 4, which falls under the good category. Overall, these findings indicate that tamarillo peel and seeds have significant potential as a sustainable source of natural textile dyes and can serve as a safer alternative to synthetic dyes.